2021
DOI: 10.1002/ajhb.23688
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in adipose development in a hunter‐gatherer population

Abstract: Objective Humans are unusually sexually dimorphic in body composition, with adult females having on average nearly twice the fat mass as males. The development of adipose sex differences has been well characterized for children growing up in food‐abundant environments, with less known about cross‐cultural variation, particularly in populations without exposure to market foods, mechanized technologies, schooling, vaccination, or other medical interventions. Methods To add to the existing cross‐cultural data, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 101 publications
(139 reference statements)
0
9
0
Order By: Relevance
“…Published results for adiposity as part of childhood growth and development among hunter‐gatherers are limited to the Baka pygmies of the Congo (Rozzi et al, 2015), and the Savanna Pume’ of Venezuela (Kramer et al, 2022). The Baka, however, have known alterations in the IGF‐1axis (Jarvis et al, 2012; Little, 2020), which affects height development and may influence the pattern of adipose development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Published results for adiposity as part of childhood growth and development among hunter‐gatherers are limited to the Baka pygmies of the Congo (Rozzi et al, 2015), and the Savanna Pume’ of Venezuela (Kramer et al, 2022). The Baka, however, have known alterations in the IGF‐1axis (Jarvis et al, 2012; Little, 2020), which affects height development and may influence the pattern of adipose development.…”
Section: Discussionmentioning
confidence: 99%
“…As a sensitivity check, curves also were fit using both a penalized spline (Suk et al 2019) and a loess smoothed curve, which were compared to those best‐fit polynomial models. Both the penalized beta spline and loess smoothed curves were produced by running a series of models with increasingly sensitive smoothing parameters and selecting the best‐fit models using AIC comparisons (Kramer et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex differences in adiposity are well known, although there are fewer studies in young children (Orsso et al, 2020): U.S. girls have been found to have slightly more fat at birth (assessing infant body composition using air displacement plethysmography) (Davis et al, 2019); and Pumé girls have been found to have more peripheral fat (triceps skinfold thickness) in childhood than boys (Kramer et al, 2021). Based on an overview paper, adipose tissue at birth and infancy has a persisting influence on adiposity in childhood and adolescence (Orsso et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Leroy and colleagues (2015) offer a mathematical explanation for age‐dependent patterns in linear growth. Regarding skinfold thicknesses specifically, Kramer et al emphasize the appropriateness of NHANES III as it is “the last known available collection of skinfold and arm circumference measurements predating the recent obesity trend in children, and has the advantage of all growth metrics being from the same cohort of children” (Kramer et al, 2021, p4). Since our purpose is comparative within a population (see also Kramer et al, 2021), we have used z ‐scores derived from NHANES III for all children in the sample.…”
Section: Methodsmentioning
confidence: 99%